Application of Autotrophic Denitrification to Nitrate-Contaminated Industrial Wastewater - Rudi Nugroho; Hirokazu Takanashi; Makoto Hirata; Tadashi Hano (ASEAN Journal of Chemical Engineering, 2003)
An autotrophic denitrification system was applied to the treatment of industrial wastewater with very low C/N ratio. The experiments were conducted by both batch suspension and continuous column runs. The denitrification behavior in suspension runs obeyed the first-order reaction with the rate constants k1and k2 of 0.014 and 0.004 m3fg-SS-d, respectively. In the continuous runs, a column was packed with a mixture of granular sulfur and limestone. The microbes mostly composed of Thiobacillus denitrificans attached on the surface of sulfur particles like biofilm with an approximate thickness of 100 1m. The denitrification rate in the packed column was expressed by a half-order equation with the rate constant of 0.172 g-Nl/2- ml/2f(kg-S d). Lower denitrification extent of industrial wastewater compared with synthetic wastewater was concluded to be caused by the lack of alkalinity.